TINDAKAN DAN MORALITAS DALAM NOVEL-NOVEL DOSTOYEVSKY - Seno Joko Suyono (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2016)
This study may be an attempt to open the new perspectives and possibilities regarding the close relationships between the literature and the philosophy. This study aims at providing a clarification about the basic problems of the philosophy (in this case: morality and actions) within the literature. The new understanding may not be reachable through certain linguistic or literary analyses. In accordance with the action and the morality found within the novels of Dostoyevsky, it can be concluded: (1) There would always be a disproportion in various levels within the characters of the novels and their actions; (2) there is a development in one of the concepts, e.g. freedom – that from one novel to another qualitatively the sense become more mature and easier to define; (3) the dynamics of the actions and the morality made from one novel to another increasingly lay in the extreme poles.